A joint optimization framework for wheat harvesting and transportation considering fragmental farmlands - P. He (Information Processing in Agriculture, 2021)
Crop harvesting and transportation should be considered as an integrated system to be optimized aiming to reduce the total operational costs. However, current studies mainly focused on how to reduce operational cost for a link, not from integrated perspective. In this paper, a joint problem which consists of harvesting and transportation problem is implemented and optimized to meet the better schedule with less operational costs. The harvesting and transportation problems could respectively be considered as a vehicle routing problem with multiple trips and a transportation problem,. These two problems should be optimized jointly because combine-harvesters and transporters should be synchronized at fragmental farmlands. A mixed integer programming is employed considering all constraints arising in the joint optimized framework. Furthermore, a hybrid algorithm is presented to find an optimum solution for this problem. Five different cases are used to verify the performance of the hybrid algorithm. Besides, our real cases are used to prove that there is a significant improvement if the integrated wheat harvesting and transportation policy is adopted. The results indicate that the model and algorithm is an effective approach to help farmers to decrease reaping costs.